Pendidikan Jiwa dalam Al-Qur’an - Khairunnisa (AL-IBNOR, 2024)
A good educational process should be aimed at Islamic values ​​originating from the Koran. Real education includes various efforts to shape a person's character so that they can control their behavior according to Islamic teachings. The main goal of education in Islam is to make humans pious people through the development of body and soul. The method used in this research is literature. The results of the research show that there are many human desires that drive their owners to evil, except for a soul that is glorified by Allah and protected from error and deviation. And education is one means of maintaining the purity of the soul.